Case Studies in Efficacy: A Reading of the Shenxian ganyu zhuan. (1st May 2013) - Halperin, Mark
Abstract : This article examines narratives from Shenxian ganyu zhuan, or " Traditions of Responsive Encounters [with] Divine Transcendents, " a collection of tales relating meetings between Daoist transcendents and humans, compiled in the early tenth century by the court Daoist, Du Guangting (850-933). In particular, the essay places the tales in their immediate historical context, namely, the political and social disorder that attended the end of the Tang. Transcendents in these stories appear less as elusive semi-deities than as active members of local society, who reward the pious and aid commoners in distress, as well as demonstrating their superior probity and practical competence vis-à-vis scholar-officials. These examples, the article argues, form part of Du's larger effort to secure state patronage for the Daoist church by illustrating Daoism's vital place in a stable, moral order.